Identifikasi Komposisi Proksimat Telur Ayam Ras Fermentasi Menggunakan Lactobacillus plantarum dengan Waktu Inkubasi yang Berbeda - A. Mangalisu; A. K. Armayanti; I. I. Arief; Z. Wulandari (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2022)
Eggs that have a balanced amino acid content can fullfill protein that needs in humans, However, eggs have a low shelf life so they were easily damaged. Fermentation technology on foodstuffs by using microbes has been widely carried out, among others using Lactobacillus bacteria. The type of Lactobacillus bacteria commonly used in egg fermentation is Lactobacillus plantarum. This study was conducted experimentally by using a completely randomized design (CRD) with 3 treatments and 3 replications each. The treatment was carried out by fermentation with an incubation temperature of 37 oC with different incubation times of 0, 48, and 96 hours with research parameters water content, crude fat, crude fiber, BETN and ash content. The results showed that different incubation time treatments on fermented chicken eggs had a significant effect (P<0.05) on water content, crude fat, crude fiber, BETN and ash content. The nutritional composition of fermented eggs by using L. plantarum could be seen from the decrease in water content, crude fiber and BETN and an increase in crude fat and ash content with increasing incubation time. The value of water content, crude fat, crude fiber, BETN and optimum ash content at an incubation temperature of 37 oC for 96 hours of incubation time.